2015
DOI: 10.4236/health.2015.74052
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Difference of Disease Prevalence in Rural China: Examples and Explanations

Abstract: Ethnic difference of disease prevalence has attracted great attentions in recent years in China, but few researches have summarized analysis available on ethnic difference of disease prevalence in rural China. The PubMed Central, Wiley Inter science, Science direct, Biomed central, CNKI and Springer-link were searched to identify studies published between January 1984 and October 2014 on ethnic inequality of health status in rural China. Distinct ethnic differences of disease prevalence exist in rural China. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Du and Keys (2015) further explained that there is not much known about the effects of dietary habits on these growing lifestyle-related conditions in China, where the dietary patterns differ greatly from those of Western populations. Guan (2015) observed that there is a high prevalence of diseases among the ethnic minority groups in rural China due to several factors among them social customs, culture, food consumption, and genetic backgrounds. Guan (2015) and Ahmed (2016) further added that the socioeconomic status of the rural ethnic groups is a major contributing factor to the health disparity between the Chinese minority ethnic groups and the majority Chinese Hans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Du and Keys (2015) further explained that there is not much known about the effects of dietary habits on these growing lifestyle-related conditions in China, where the dietary patterns differ greatly from those of Western populations. Guan (2015) observed that there is a high prevalence of diseases among the ethnic minority groups in rural China due to several factors among them social customs, culture, food consumption, and genetic backgrounds. Guan (2015) and Ahmed (2016) further added that the socioeconomic status of the rural ethnic groups is a major contributing factor to the health disparity between the Chinese minority ethnic groups and the majority Chinese Hans.…”
Section: Introductionmentioning
confidence: 99%
“…Guan (2015) observed that there is a high prevalence of diseases among the ethnic minority groups in rural China due to several factors among them social customs, culture, food consumption, and genetic backgrounds. Guan (2015) and Ahmed (2016) further added that the socioeconomic status of the rural ethnic groups is a major contributing factor to the health disparity between the Chinese minority ethnic groups and the majority Chinese Hans. Research by Fu, Wang, and Wang (2005) reported differences in food consumption patterns and nutrient intake were also found in groups divided in line with their gender, residence, and household income.…”
Section: Introductionmentioning
confidence: 99%